Describing and exploring self‐esteem, physical self‐perceptions, physical activity and self‐efficacy in adolescent and young adult cancer survivors. (24th October 2019) - Wurz, Amanda; Brunet, Jennifer
Abstract: Objectives: (a) Describe levels of physical and global self‐esteem and (b) explore the relationships between these types of self‐esteem and physical activity (PA) behaviour, self‐efficacy for PA and physical self‐perceptions among adolescent and young adult (AYA) cancer survivors. Methods: A total of 87 AYA cancer survivors ( M age = 32.90 ± 4.38 years), who were on average 2.08 ± 1.37 years post‐treatment, participated in this cross‐sectional observational study. Descriptive statistics, correlations and hierarchical multivariate linear regression analyses were used to analyse the data. Results: Moderate levels of physical and global self‐esteem were reported. Both types of self‐esteem were significantly related to physical self‐perceptions, but not to PA behaviour nor self‐efficacy for PA. Self‐efficacy for PA moderated the relationship between physical self‐perceptions and physical self‐esteem, such that the association between physical self‐perceptions and physical self‐esteem was of stronger magnitude at higher levels of self‐efficacy for PA than at lower levels of self‐efficacy for PA. Conclusion: This study provides a starting point for describing self‐esteem and identifying the circumstances under which self‐esteem may be optimised among AYA cancer survivors. Fostering feelings of confidence, competence and control over PA may help to promote psychological well‐being among AYA cancer survivors.